Transformasi Pendidikan sebagai Investasi Sumber Daya Manusia: Studi Fenomenologis atas Pengalaman Individu dalam Produktivitas Kerja - Nur Rahma Al Adawiyah; Sari Agustina; Nurochim; Sita Ratnaningsih (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2026)
This study aims to analyze how educational transformation is interpreted as an investment in human capital to enhance labor productivity in the digital era. Previous studies have mainly examined the relationship between education and productivity through quantitative macro-level indicators, while individuals’ subjective experiences in interpreting education as human capital investment remain underexplored. This study employed a qualitative approach with a phenomenological design to understand participants’ lived experiences in digital-based learning and work contexts. Data were collected through semi-structured interviews, observation, and documentation involving five participants selected through purposive and snowball sampling. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal five main themes: the shift toward self-directed learning, the relevance of education to labor market needs, the internalization of moral and spiritual values in shaping work ethics, adaptability to technological change, and the formation of professional identity. These findings indicate that educational transformation does not automatically improve labor productivity. Its effectiveness depends on how individuals internalize, interpret, and apply their learning experiences in real work situations. This study contributes to human capital and Islamic education management studies by emphasizing the role of subjective experience, values, and adaptability in linking education with productivity. Future research is recommended to involve more diverse participants and apply mixed-method approaches to obtain a broader understanding of educational transformation.